165k views
0 votes
What is the answer please 3(1 + h) =

User Synthaze
by
5.9k points

2 Answers

4 votes

Answer:

3 + 3h

Explanation:

Apply the Distributive Property of Multiplication:

3(1 + h) = 3 + 3h

User Webx
by
4.9k points
5 votes

Answer:

3h + 3

Explanation:

Distribute 3 to all terms within the parenthesis, and multiply:

3(1 + h) =

3(1) = 3

3(h) = 3h

3h + 3 is your answer.

~

User Mahbaleshwar Hegde
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.